Fetal cardiac parameters for prediction of twin‐to‐twin transfusion syndrome. (10th September 2014) - Zanardini, C.; Prefumo, F.; Fichera, A.; Botteri, E.; Frusca, T.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 44: 386–387